Operator ideal of s-type operators using weighted mean sequence space - Erdogan, Ezgi; Karakaya, Vatan (NORTH UNIV BAIA MARE, 2017)
We introduce a different class of s-type operators by using the generalized weighted mean sequence space co (u, v), then it is shown that this new class of operators is a quasi-Banach operator ideal. Moreover, their injectivity and surjectivity are investigated according to sort of s-number. Finally, we proof that it is a dosed operator ideal under some conditions.
Keywords: Operator ideals; s-numbers; weighted mean sequence space; Mathematics